2018
DOI: 10.1016/j.jspd.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Does School Screening Affect Scoliosis Curve Magnitude at Presentation to a Pediatric Orthopedic Clinic?

Abstract: Level 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(26 reference statements)
0
6
0
3
Order By: Relevance
“… 14 No publications included in the task force evaluated the benefits of screening for AIS on severity of curvature compared with no screening. Thomas et al 15 compared the curve magnitude at initial presentation for evaluation of scoliosis for new patients between 1994-2004 (during school screening) and 2004-2014 (after school screening) and found that after school screening was discontinued, mean curve magnitude at presentation statistically increased. Consistent with their results, our study and that by Goldstein et al 7 collectively imply the importance of scoliosis screening for early curves detection.…”
Section: Discussionmentioning
confidence: 99%
“… 14 No publications included in the task force evaluated the benefits of screening for AIS on severity of curvature compared with no screening. Thomas et al 15 compared the curve magnitude at initial presentation for evaluation of scoliosis for new patients between 1994-2004 (during school screening) and 2004-2014 (after school screening) and found that after school screening was discontinued, mean curve magnitude at presentation statistically increased. Consistent with their results, our study and that by Goldstein et al 7 collectively imply the importance of scoliosis screening for early curves detection.…”
Section: Discussionmentioning
confidence: 99%
“…“Distribution of curves was similar for children detected through school-based screening compared to those who were detected clinically”[ 26 ]. And the effectiveness of school screening on curve magnitude at clinical presentation, in comparison to clinically detected cases, is reported as doubtful[ 39 ].…”
Section: Updated Recommendations Outdated Standards?mentioning
confidence: 99%
“…In the last decade, in the new era of guideline development[ 10 - 12 , 27 , 28 ], and after screening principles have evolved significantly[ 1 , 8 , 9 , 29 , 30 ], a number of updated and new recommendations and statements on screening for scoliosis[ 31 - 35 ], as well as on periodic examination of the spine[ 36 ], have been released. Nonetheless, the dilemmas prevail[ 37 - 39 ] and consensus does not seem to be reached[ 40 , 41 ]. Internationally, recommendations differ substantially, not only in terms of their content, but also standards of development and screening principles.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospectively studying the referral patterns of suspected cases of AIS in orthopaedic clinics, our team [5,9,10] demonstrated that after discontinuation of school screening programs, 20% of patients were referred "late" to a scoliosis clinic to benefit from appropriate and timely conservative management with a spinal brace. Thomas et al reported that in a US county, the number of referrals to orthopaedic clinics for scoliosis in areas without school screening decreased, as well as the number of spinal brace prescriptions [11].…”
Section: Introductionmentioning
confidence: 99%